Nearly one-fold enhancement in photoluminescence quantum yield for isostructural zero-dimensional hybrid antimony(iii) bromides by supramolecular interaction adjustments. Issue 12 (9th March 2022) - Peng, Ying-Chen; Zhou, Sheng-Hua; Jin, Jian-Ce; Gu, Qi; Zhuang, Ting-Hui; Gong, Liao-Kuo; Wang, Ze-Ping; Du, Ke-Zhao; Huang, Xiao-Ying
Abstract : A nearly one-fold enhancement of photoluminescence quantum yields (PLQYs) owing to the supramolecular interaction adjustments in two isostructural zero-dimensional hybrid antimony(iii ) bromides with deep-red emission is presented. Abstract : Zero-dimensional (0D) organic–inorganic metal halides (OIMHs) hold promise in photoluminescence properties and related applications. Thus far, the photoluminescence quantum yields (PLQYs) of the reported 0D hybrid antimony(iii ) bromides (HABs) are not as high as those of the chloride analogs; therefore, the improvement of PLQY is an important issue for luminescent HABs. Herein, a supramolecular interaction adjustment strategy to improve the PLQYs of HABs is proposed. Two isostructural 0D HABs that crystallize with different lattice solvent molecules, namely [EtPPh3 ]2 [SbBr5 ]·EtOH (1·EtOH-Br ; EtPPh3 = ethyltriphenylphosphonium; EtOH = ethanol) and [EtPPh3 ]2 [SbBr5 ]·MeCN (1·MeCN-Br ; MeCN = acetonitrile), have been synthesized. Both of them exhibit typical self-trapped exciton (STE) photoluminescence (PL) with broad emission, a large Stokes shift and a long lifetime. They show deviation in deep-red emission peaks (655 nm vs. 661 nm) owing to the difference in the distortion level of [SbBr5 ] 2− anions. Most importantly, 1·EtOH-Br exhibits a nearly one-fold enhancement in PLQY compared to 1·MeCN-Br (18.26% vs. 9.29%). Density functional theory (DFT) calculations, hydrogen bonding analysis and Hirshfeld surface analysis suggest that the PLQY enhancement is due to the structural rigidity improvement brought by hydrogen bonding adjustments between the inorganic [SbBr5 ] 2− anions and solvent molecules. This work provides a new insight into the structure–property relationship study and PLQY improvement for 0D OIMHs.